2018
DOI: 10.1177/1934578x1801300625
|View full text |Cite
|
Sign up to set email alerts
|

Isolation a Homogalacturonan from the Outer Seed Coat of Shaddock (Citrus grandis Osbeck)

Abstract: An acidic mucilage was isolated from the outer-layer seed coat of shaddock (Citrus grandis Osbeck) by water extraction at room temperature, and purified by DE-52 anion-exchange chromatography using 0.26  0.37 M NaCl. This purified mucilage was almost entirely composed of galacturonic acid residues. Glycosyl-linkage analysis showed that the backbone was 14 linked. Fourier Transform Infrared Spectroscopic analysis and determination of the degree of methylation further revealed that the mucilage was a low-degre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…However, studies about the physicochemical properties of this potential mucilage are quite limited. Wang et al [ 20 , 21 ] isolated a low-degree (11.94%) esterified homogalacturonan from the outer-layer seed hull of CGO by water extraction and found that it exhibited some bioactivities such as antioxidant activity and stimulation of the proliferation of NIH3T3 cells. The objective of this study is to further investigate the structural and functional properties of the mucilage from the seed of CGO as a function of extraction procedures involving ultrasonic and cellulolytic enzyme-assisted extractions (cellulase or Celluclast ® 1.5 L).…”
Section: Introductionmentioning
confidence: 99%
“…However, studies about the physicochemical properties of this potential mucilage are quite limited. Wang et al [ 20 , 21 ] isolated a low-degree (11.94%) esterified homogalacturonan from the outer-layer seed hull of CGO by water extraction and found that it exhibited some bioactivities such as antioxidant activity and stimulation of the proliferation of NIH3T3 cells. The objective of this study is to further investigate the structural and functional properties of the mucilage from the seed of CGO as a function of extraction procedures involving ultrasonic and cellulolytic enzyme-assisted extractions (cellulase or Celluclast ® 1.5 L).…”
Section: Introductionmentioning
confidence: 99%